Antioxidant and Anti-atherogenic Properties of Prosopis strombulifera and Tessaria absinthioides Aqueous Extracts: Modulation of NADPH Oxidase-Derived Reactive Oxygen Species - Isabel Quesada (Frontiers in Physiology, 2021)
Despite popular usage of medicinal plants, their effects as cardiovascular protective agents have not been totally elucidated. We hypothesized that treatment with aqueous extract from Prosopis strombulifera (AEPs) and Tessaria absinthioides (AETa), Argentinian native plants, produces antioxidant effects on vascular smooth muscle cells (VSMCs) and attenuates atherogenesis on apolipoprotein E-knockout (ApoE-KO) mice. In VSMCs, both extracts (5–40 μg/ml) inhibited 10% fetal calf serum-induced cell proliferation, arrested cell in G2/M phase, reduced angiotensin II-induced reactive oxygen species (ROS) generation, and decreased NADPH oxidase subunit expression. In ApoE-KO mice, extracts significantly reduced triglycerides and lipid peroxidation [plasma thiobarbituric acid reactive substances (TBARS)], increased plasma total antioxidant status (TAS), and improved glutathione peroxidase activity in the liver. Under high-fat diet (HFD), both extracts were able to inhibit O2– generation in the aortic tissue and caused a significant regression of atheroma plaques (21.4 ± 1.6% HFD group vs. 10.2 ± 1.2%∗ AEPs group and 14.3 ± 1.0%∗ AETa group; ∗p < 0.01). Consumption of AEPs and AETa produces antioxidant/antimitogenic/anti-atherosclerotic effects, and their use may be beneficial as a complementary strategy regarding cardiovascular disease therapies.